A proposed approach for analyzing post-study therapy effect in survival analysis. Issue 4 (3rd July 2016) - Luo, Xiaolong; Li, Mingyu; Wu, Chengqing; Xu, Qiang; Chen, Guang; Dornseif, Bruce E.; Renschler, Markus F.; Koch, Gary
ABSTRACT: Clinical trials that explore long-term endpoints may confound the analysis when post-study therapy effects are considered. This article introduces a procedure to mediate the effects of confounding and allow inferences of first-line experimental treatments in the presence of post-study therapy. The procedure is evaluated by intensive simulation analyses and applied to an analysis of a clinical cancer trial.